2015
DOI: 10.1108/qae-05-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Chilean universities and institutional quality assurance processes

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
(31 reference statements)
1
12
0
6
Order By: Relevance
“…In contrast to previous research conducted by Marasabessy (2008), Abroza (2015), and Asy'ari (2013), which found evidence that quality assurance affects organizational performance, the findings of this study prove the opposite relationship. Meanwhile, related to the significant relationship between organizational culture and organizational performance both directly and indirectly mediated by quality assurance, this study justifies several previous theories which show that organizational culture is an important predictor of the creation of systems that can encourage high organizational performance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016).…”
Section: Organizational Culture Quality Assurance and Organizationasupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast to previous research conducted by Marasabessy (2008), Abroza (2015), and Asy'ari (2013), which found evidence that quality assurance affects organizational performance, the findings of this study prove the opposite relationship. Meanwhile, related to the significant relationship between organizational culture and organizational performance both directly and indirectly mediated by quality assurance, this study justifies several previous theories which show that organizational culture is an important predictor of the creation of systems that can encourage high organizational performance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016).…”
Section: Organizational Culture Quality Assurance and Organizationasupporting
confidence: 84%
“…Recent literature reviews have explored themes that drive organizational performance, especially HEIs performance such as effective leadership (Alonderiene and Majauskaite, 2016;Awuzie and Emuze, 2017;Spendlove, 2007), organizational culture (Haryono and Arafat, 2017;Ibrahim et al, 2018;Imam et al, 2013), and quality assurance (López et al, 2015;Lyytinen et al, 2017;Martin, 2016;Mourad, 2017;Prakash, 2018;Sadler, 2017;Santos and Dias, 2017;Tam, 2001;Yingqiang and Yongjian, 2016). However, some literature fails to prove that leadership has an influence on performance (Sihombing et al, 2018) and organizational culture (Shiva and Suar, 2012).…”
Section: Literature Review Transformational Leadershipmentioning
confidence: 99%
“…Estos resultados son congruentes con otras evidencias de consistencia y homogeneidad entre estos tipos de instituciones de Educación Superior si se consideran variables del desempeño académico en acreditación institucional o aprendizaje institucional en procesos de aseguramiento de la calidad 11,21,[28][29][30] . Desde esta perspectiva resulta importante establecer la relación entre calidad y tipos de universidades, considerando que las clasificaciones de éstas tienen efecto en el financiamiento público, lo que genera controversias y propuestas de nuevas clasificaciones de universidades 29,31-33. Las diferencias institucionales pueden responder a factores culturales, organizacionales y de gestión que interactúan en los procesos de aseguramiento de la calidad [32][33][34][35] . En años recientes, en Chile, se han establecido cambios dado que algunas de las nuevas universidades privadas se han integrado al CRUCH y al sistema de selección de estudiantes, debiendo cumplir con requisitos de calidad y gestión.…”
Section: Discussionunclassified
“…Por tanto, la disposición de beneficios asistenciales puede ser tomada como medida de calidad de una institución de educación superior, sobre todo cuando es parte de una política pública de inclusión mayor. Política pública que es parte de la consistencia externa de la calidad según López, Rojas, López y López (2015) y Rojas y López (2016). De esta manera, preocuparse de la calidad de la educación superior conlleva conocer las dificultades y facilidades para el buen rendimiento estudiantil, conocimiento que orientaría de mejor manera el uso de los recursos públicos (Garbanzo, 2007a).…”
Section: Discusión Y Conclusiónunclassified